2003
DOI: 10.1016/s0014-5793(03)01101-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of coupling proton movements to c‐ring rotation in ATP synthase

Abstract: F 1 F 0 ATP synthases generate ATP by a rotary catalytic mechanism in which H + transport is coupled to rotation of an oligomeric ring of c subunits extending through the membrane. Protons bind to and then are released from the aspartyl-61 residue of subunit c at the center of the membrane. Subunit a of the F 0 sector is thought to provide proton access channels to and from aspartyl-61. Here, we summarize new information on the structural organization of Escherichia coli subunit a and the mapping of aqueous-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 33 publications
1
115
0
Order By: Relevance
“…Atp6p is a key subunit of the F O proton-translocating domain of the ATP synthase. Proton movements mediated by Atp6p lead to the rotation of a transmembrane ring of Atp9p subunits (referred to as subunit c in humans) which ends up in conformational changes at the level of the catalytic sites in the F 1 extra-membrane domain of the enzyme that favor the synthesis ATP and its release into the mitochondrial matrix [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Atp6p is a key subunit of the F O proton-translocating domain of the ATP synthase. Proton movements mediated by Atp6p lead to the rotation of a transmembrane ring of Atp9p subunits (referred to as subunit c in humans) which ends up in conformational changes at the level of the catalytic sites in the F 1 extra-membrane domain of the enzyme that favor the synthesis ATP and its release into the mitochondrial matrix [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The rotation enables cooperative interactions between three catalytic sites, each in the b subunits with different conformations. The conformational asymmetry of the three b subunits was suggested biochemically by affinity labeling, chemical crosslinking, and reconstitution from isolated subunits, as reviewed previously (1)(2)(3)(4)(5). The first high-resolution X-ray structure of the F 1 sector from bovine heart mitochondria clearly showed that the three b subunits in F 1 have different catalytic site conformations (7).…”
Section: Introductionmentioning
confidence: 90%
“…We focus mainly on E. coli F-ATPase rotational catalysis, taking advantage of its easy purification (21), and the accumulated biochemical results for the wild-type and mutant enzymes (2)(3)(4)(5). It should be noted that this enzyme can be studied thermodynamically in the physiological temperature range (10-40 C) of the organism.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations